The activity of a psychology teacher in the process of ensuring the psychosomatic health of students - Karmanova, Zh.A.; Autayeva, I.; Koshkumbaev, K.T. (Karaganda University named after academician E.A.Buketov, 2023)
The article examines the activity of a psychology teacher in the process of ensuring the psychosomatic health of students. The authors analyze the factors that have an impact on the psychosomatic health of adolescents in the educational process of school. Each factor is considered from the standpoint of its importance for ensuring the psychosomatic health of students, as well as negative disorders resulting from adverse effects. The conclusion describes the psychological and pedagogical conditions for the prevention and correction of psychosomatic disorders of adolescents, aimed at the formation of safe and health-preserving behavior in them.
Білім алушылардың психосоматикалық денсаулығын қамтамасыз ету процесінде педагог-психологтың қызметі
Деятельность педагога-психолога в процессе обеспечения психосоматического здоровья обучающихся
Keywords: psychosomatic health; psychosomatic disorders; psychological and pedagogical conditions; school educational process; prevention and correction of psychosomatic disorders; risk factors for psychosomatic health disorders